COMPARATIVE STUDY BETWEEN JUST JUMP AND OPTOJUMP - Trofin F.; Honceriu C. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
Performance sport requires higher and higher physical demands, the explosive component becoming an increasingly important role. Explosive force can be tested with instruments that can have more or less accuracy. The Just Jump system is one of them, based on the method of determining the height of the jump by using the flight time. This study aims to help adjust the results displayed by Just Jump during use to determine the explosive strength of the lower limbs so that they are as accurate as possible. A lot of 14 female handball players (19,21±1,47 ani, 172±5,14 cm, 69,21±4,3) was tested with the help of Just Jump and Optojump, and a high-precision system, to determine the equation that can adjust the results of the first one. The paper has a practical application, given the trend of continuous monitoring of progress of athletes during the training program. The pressure mat through its physical features, jumping biomechanics, and geographic parameters of the area where the test applies can influence the result displayed by the Just Jump center unit. Consequently, we determined a corrective formula for Just Jump results by reference to Optojump.